#TITLE_ALTERNATIVE# - T, Parsaoran
S area PT.Chevron Indonesia Minas region is one of the oil field in Indonesia, located at Central Sumatra Basin. The primary reservoir is Sihapas Group with sand lithology, and the primary trap is structure geology. Gravity method was carried out to identified the subsurface structure from Bouguer Anomaly. Data acquisition was designed with space of measuring 100 m and 200-250 m and covered 6 x4 km2 area. Processing data results 0 to 9 mGal of Bouguer anomaly. Quantitative analysis was carried out using spectral analysis with window 1000 m x 1000 m, and produce 2 to 9 mGal of Bouguer anomaly. Bouguer anomaly map shows structures fault with north-south orientation. SVD analysis and forward modeling identified normal fault, with dip of the fault plane are W and E direction. Forward modeling using 5 layers describe strathigraphic area S ,that consist of Basement, Pematang Formation, Sihapas Group, Petani Formation, and Minas Formation.